Analisis Konsumsi BBM dengan Variasi Lingkungan Operasi Kendaraan Bermotor Menuju Perilaku Eco-Drive - Syarifudin, Mohammad; Muhammat Abdul Fatah, Kemas; Dalimunthe, Ruslan; Mohammad Syarifudin; Fatah, Kemas Muhammat Abdul; Ruslan Dalimunthe (P3M Politeknik Negeri Cilacap, 2023)
The increase in greenhouse gases in the form of CO2 gas as vehicle exhaust emissions contributes to climate change. Technological approaches and alternative fuels continue to reduce fuel consumption, but this is not enough. Another method is to use eco-drive behavior, one of which is related to replacing the air filter. This study is purposed to provide guidelines for motorized vehicles operating in selected areas in Lampung Province in the behavior of eco-driving. The results of the fuel consumption test using the full-to-full method found that at each filter distance (8,000 km, 12000, and 16,000 km), vehicles operating in Mesuji with the highest deficiency, followed by Tanjung Bintang and Krui areas. In line with eco-drive behavior, for vehicles operating in Mesuji, the air filter replacement period must be faster than the other two areas, followed by Tanjung Bintang and Krui.